Dion and the Argead expansion - Diego Chapinal-Heras (Karanos)
The aim of this study is to examine the expansion of the Argead kingdom of Macedon over the region of Pieria, and the role played by the sacred city of Dion in this process. Despite northern Pieria belonging to the core of the Macedonian realm, southern Pieria did not fall under Macedonian sway until the end of the Archaic Age. By using evidence from both literature and archaeology, this paper attempts to reconstruct the assimilation of southern Pieria into the Macedonian kingdom and the way that influenced the development of Dion.